Ovum Pick-Up and In Vitro Embryo Production from Stimulated Vs Non-Stimulated Buffaloes - Patil, Sanket P.; Hadiya, Kamlesh K.; Layek, Siddhartha S.; Gorani, Sanjay; Raj, Sudharson; Karuppanasamy, Kuppusamy; Dhami, Arjun J.; Gupta, Rajesh Onkarnath (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The effect of ovarian stimulation prior to ovum pick-up (OPU) is yet to be fully assessed in buffaloes. Hence the present study was designed to assess the effect of different ovarian stimulation regimes before OPU on in vitro embryo production (IVEP) in buffaloes. Nine selected donor buffaloes were equally and randomly allocated to two stimulation protocols (SP1 and SP2) and a non-stimulated control. In the SP1 group, an intravaginal progesterone device (CIDR) was inserted along with Estradiol Benzoate (2.0 mg, im) on a random day of the estrous cycle (Day 0). In SP2 group, two PGF2α injections were administered im 11 days apart, followed by 10 µg GnRH im on day 14. In SP1 on days 4 and 5, and in SP2 on days 16 and 17, buffaloes were administered a total of FSH 200 mg im, divided in four tapering doses at 12 hours interval (57, 57, 43, and 43 mg). In the control group, OPU sessions were performed on day 10 of PGF2α induced estrus, while OPU sessions were carried out after 52 hours of coasting period in SP1 and SP2 groups. Two OPUs were carried out on each donor across experimental groups. Means of different groups were compared using one-way ANOVA using a general linear model. Although a mean number of follicles aspirated per buffalo remained similar across all groups (22.0 ± 6.9 vs. 22.0 ± 6.0, 21.2 ± 5.8; p = 0.99), a mean number of oocytes recovered/buffalo/OPU (14.8 ± 7.8 vs. 11.5 ± 3.4, 7.8 ± 2.3; p = 0.63) and oocyte recovery rate (59.2 ± 13.2 vs. 54.5 ± 4.8, 36.7 ± 3.4%; p = 0.17) was higher in the control group compared to both the stimulated groups. Attributing to ovarian stimulation in both the stimulated groups, the cleavage rate (39.2 ± 10.1 vs. 66.3 ± 7.8, 68.9 ± 10.1%; p = 0.07) and blastocyst rate (8.7 ± 5.3 vs. 32.1 ± 8.9, 17.3 ± 7.1%; p = 0.10) were higher compared to the control group. The highest embryos/OPU (1.3 ± 0.8, 3.3 ± 1.0, 1.5 ± 0.6; P = 0.23) were achieved in SP1 group as compared to Control and SP2 groups. The results indicate that ovarian stimulation increases oocyte quality, especially when stimulated in the presence of exogenous luteal support, translating into better and cost-efficient IVEP in buffaloes.